Comparison of the effect of topical bevacizumab and sorafenib in experimental corneal neovascularization - Yildirim, Hakan; Aydemir, Orhan; Balbaba, Mehmet; Ozercan, Ibrahim Hanifi; Ilhan, Nevin (Taylor & Francis Ltd, 2020)
Purpose: The purpose of this study was to compare the neovascularization inhibiting the effect of topical bevacizumab and sorafenib and to determine the effective dose of sorafenib. Material and Methods: Forty-two healthy Wistar albino rats were randomly divided into six groups. The right corneas of all rats except group 1 were cauterised with silver nitrate. Group 2 received DMSO, group 3 received topical bevacizumab (5 mg/dL, 3 times a day) and group 4, 5 and 6 received topical sorafenib (2.5 mg/dl, 5 mg/dL, 7.5 mg/dL, 2 times a day respectively), between days 1 and 7. Corneal photographs were taken on day 8 and the corneal neovascular area percentage was calculated. Following decapitation, the corneas were removed to determine the levels of VEGF ELISA and corneal immune staining. The Mann-Whitney U-test was used for statistical analysis Results: The neovascular corneal area percentage was statistically significantly lower in the treatment groups than group 2 (p < 0.05). The intensity of VEGF immune staining was also lower in groups 3, 5 and 6 from the group 2. Group 3, 5 and 6 were no significant differences compared to group 1. The VEGF ELISA levels were statistically significantly lower in group 3, 5 and 6 compared to group 2 (p < 0.05). There was no statistically difference between VEGF ELISA levels of group 2 and 4 (p > 0.05) Conclusions: Sorafenib was as effective as bevacizumab in the regression of corneal neovascularization. The effect of sorafenib seems to be dose-dependent. The low doses and twice a day administration are important advantages of sorafenib.
Keywords: Corneal neovascularization; sorafenib; bevacizumab